La Escala de Inteligencia para Niños de Wechsler y las variantes socio-culturales - Thorne, Cecilia (1988)
The authors wam on the danger of using pseudo-adaptations in intelligence testing. A reference to the Wechsler Scales and the WlSC-R is done in the first place. Secondly, sorne Spanish adaptations of the test are mentioned. Finally, a bibliographical review conceming socio-cultural studies is presented. In these studies the emphasis is on the discrepancy that exists in different ethnic groups and populations.